A scoping review of measurement tools and a content validity evaluation of the University of Jyvaskyla Active Aging Scale (UJACAS). - Napoletano, Rosa; Lopez, Antonella; Traficante, Sergio; Ricciardi, Elisabetta; Tinella, Luigi; Caffò, Alessandro Oronzo; Bosco, Andrea; Spano, Giuseppina (European Journal of Ageing, 2025)
The concept of active aging (AA) was defined as the process of optimizing opportunity for health, security, and social participation for older people. While several questionnaires were developed to measure AA, there is no universal consensus on how to measure it, underlining a lack of clarity about what aspects to consider in the evaluation. To contribute to fill this gap, the aims of these two studies were to provide a guide for aging care professionals to choose the most appropriate questionnaire(s) based on a scoping review of the specialist literature and on a content analysis of the questionnaire, that is, the University of Jyvaskyla Active Aging Scale (UJACAS). Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines were used. We found 25 records introducing questionnaires. The content validity evaluation of the most complete questionnaire (in terms of inspected content areas), i.e., UJACAS, was conducted to obtain a complete framework of evaluated aspects. Among the selected questionnaires, heterogeneity was found regarding investigated aspects and relative terms used to describe it. Only two questionnaires were found to be validated in other languages besides the original one. The content validity evaluation of UJACAS revealed its comprehensiveness in covering various aspects of AA. Specifically, five items mainly addressed one content area, while the others encompassed more than one content area. In terms of assessed aspects and translations, the UJACAS scale could be considered the most complete questionnaire for AA evaluation. Furthermore, recognizing the heterogeneity of the terms related to the aspects investigated could help professionals in selecting assessment tools with greater precision.